Festiwale – święta sztuki czy projekty intelektualne - Joanna Ostrowska, Joanna Ostrowska (Człowiek i Społeczeństwo, 2012)
The article tries to analyze the phenomenon of the growing numbers of artistic festivals with an intellectual agenda. In the author's opinion the very appearance of artistic festivals in the beginning of the 20th Century was already an intellectual project of healing war wounds through art, which later created the background for the political project of a common union of European countries. Contemporary artistic festivals are as much presentations of different kinds of art as they are intellectual projects that try to introduce various issues: urban studies, ethnical diversity or results of scientific research. Artistic festivals are analyzed here as cultural performances (in order to be presented, issues undertaken by the festivals need to be performed) that have subversive, transformative and normative power. From the viewpoint of performance studies and aesthetics of performativity, contemporary festivals crushed the division between art and events that are part of everyday, "real" life.